The historical approach, its origins, and how it was transferred to literature, Taha Hussein, as a model - عبد الكريم النفّاخ (آداب الكوفة, 2012)
The researchers almost agree that the approach is the path that the researcher takes to reach the truth and present it to the recipient, whether he is a specialist or not ( ); And man as a living being granted by God the mind and intelligence; There is no doubt that this creature knew the methodology, but it is an unorganized methodology, lacks deduction and analysis, and tends to individual naivety. For them, this word meant (research, consideration, or knowledge). . And from here